INTERFAITH MARRIAGE DALAM PERSPEKTIF AL-QUR’AN DAN SUNNAH - M. Burhanuddin Ubaidillah; M. Adib Atho’urrochim (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
There is no concrete definition of Interfaith Marriage other than marriages conducted where each bride and groom have different religious beliefs, because basically interfaith marriages or mixed marriages are prohibited both by positive law and by the laws of each religion in Indonesia . The phenomenon raised by Nurcholish in his work Menjawab 101 Masalah Nikah Beda Agama proves that many couples hold interfaith marriages both in Indonesia and not in other countries. The interfaith marriage referred to here is the marriage of a Muslim man to a non-Muslim woman or vice versa, the marriage of a Muslim woman to a non-Muslim man. Therefore, there is a need for a comprehensive explanation of the law on interfaith marriages. This article focuses on three types of interfaith marriage in the perspective of the Koran and Sunnah. First, the marriage of a Muslim man to a polytheist woman (musyrikah). Second, the marriage of Muslim men to Ahl al-Kitab (Kitabiyyah) women. Third, the marriage of Muslim women to non-Muslim men, whether polytheists or Ahl al-Kitab (Kitab).